2004
DOI: 10.1111/j.0013-9580.2004.17004.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency Oscillations after Status Epilepticus: Epileptogenesis and Seizure Genesis

Abstract: Summary:Purpose: To investigate the temporal relation between high-frequency oscillations (HFOs) in the dentate gyrus and recurrent spontaneous seizures after intrahippocampal kainite-induced status epilepticus.Methods: Recording microelectrodes were implanted bilaterally in different regions of hippocampus and entorhinal cortex. A guide cannula for microinjection of kainic acid (KA) was implanted above the right posterior CA3 area of hippocampus. After recording baseline electrical activity, KA (0.4 µg/0.2 µl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
272
4
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(300 citation statements)
references
References 23 publications
22
272
4
2
Order By: Relevance
“…Distinct HFOs have been closely linked to areas of seizure onset and epileptogenic areas (Bragin et al, 2002b(Bragin et al, , 2004Jacobs et al, 2008Jacobs et al, , 2009a. Additionally, spikes co-occurring with HFOs were more exact in predicting the SOZ than spikes in general.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct HFOs have been closely linked to areas of seizure onset and epileptogenic areas (Bragin et al, 2002b(Bragin et al, , 2004Jacobs et al, 2008Jacobs et al, , 2009a. Additionally, spikes co-occurring with HFOs were more exact in predicting the SOZ than spikes in general.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal epileptiform activity has been recorded from the EC region 91,92 and is reported to be the lead structure in the emergence of tonic discharges in mesial structures in a majority of patients with EC atrophy. 93,94 Some studies have reported neuronal loss and gliosis in superficial layers of the EC, 86 whereas others find no significant difference in neuronal densities in the EC of patients with and without hippocampal sclerosis.…”
Section: Astrocytes May Contribute To the High Glutamate Levels At Thmentioning
confidence: 99%
“…They have been associated with epileptogenesis as they occur before the first seizure in the kainic acid rat model (Bragin et al, 2004a). HFOs appear to co-localize with the seizure onset zone (SOZ), which suggests that they are involved in seizure genesis (Bragin et al, 2004b;Jacobs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, removal of HFO generating tissue is related to good surgical outcome, more than spikes and the SOZ are (Jacobs et al, 2010), which supports their relation to epileptogenic tissue and potential clinical importance. The current hypothesis is that HFOs result from misconnected or disinhibited neuronal networks leading to highly synchronized neuronal activity over an area of brain tissue, which in turn results in seizure genesis after other areas or networks get involved (Bragin et al, 2004a;Engel et al, 2009;Ogren et al, 2009). …”
Section: Introductionmentioning
confidence: 99%